Can computer-guided surgery help orthodontics in miniscrew insertion and corticotomies? A narrative review - Guarnieri, Rosanna; Grenga, Camilla; Altieri, Federica; Rocchetti, Federica; Barbato, Ersilia; Cassetta, Michele (Frontiers in Oral Health, 2023)
Orthodontics has considerably increased the use of technology combined with surgery as a support to improve dental movements both in terms of predictability, acceleration of movement and fewer side effects. To achieve these goals, miniscrews and corticotomy were introduced, which application can be optimized through a digital workflow that permits to increase the accuracy of surgical and orthodontic set-up. The tool that transfers the information is the CAD/CAM (Computer-Aided Design/ Computer-Aided Manufacturing) template. Aim of this review is to illustrate the use of the computer guided surgery in orthodontics regarding miniscrews and piezocision. The search strategy was a combination of Medical Subject Headings (Mesh) and free-text words for PubMed. 27 articles were included in review: 16 concerned miniscrews and 11 concerned corticotomy. Nowadays the need of faster treatments, the improved systems of anchorage and the evolution of the imaging technologies require the knowledge of the digital workflow. CAD/CAM templates allows greater precision and predictability of miniscrews insertion even in the hands of less experienced clinicians and permit a better orientation and depth of cortical incision. In conclusion digital planning makes surgery faster and easier and helps to identify and correct potential problems before the procedure.